2022
DOI: 10.1155/2022/5894416
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Lagerstroemia speciosa Ameliorated Blood Pressure in LNAME Induced Hypertension in Experimental Rats through NO/cGMP and Oxidative Stress Modulation

Abstract: Cardiovascular disease is the primary reason for chronic heart diseases and mortality worldwide. Hypertension (HTN) is the utmost dominant risk factor for the evolution of several diseases. Herbal medicines, traditional medicinal herbs, and their extracts are widely utilized to treat and monitor HTN. Herbal components have been shown to help relax arteries and lower oxidative stress. The current study assesses the probable role of herbal plant extract Lagerstroemia speciosa (LS) in the LNAME induced HTN in rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%